Topics in Copular Clauses - Bartošová, Jitka (My University, 2017)
This dissertation investigates syntax and semantics of copular clauses containing two NPs. Since Higgins (1973) four semantically distinct types of copular clauses have been recognized in the literature, i.e. predicational, equative, specificational, and identificational clauses. There are many proposals aiming to reduce the number of copular clause types via collapsing certain types into others. This dissertation contributes to the debate by providing novel evidence from Czech that identificational clauses are predicational and specificational clauses are inverted predicational or equative clauses. Czech provides an excellent tool to investigate copular clauses for three reasons: (i) rich phi-feature agreement, (ii) case alternation, (iii) analytical verbal morphology. Using the three properties Czech offers, I argue that specificational clauses are derived via scrambling of a structurally lower NP over a structurally higher NP. Consequently, I support the inversion analysis of specificational clauses (Moro, 1997; Den Dikken, 2006; Mikkelsen, 2006; Heycock, 2012, a.o.). I also argue that specificational clauses may be derived from both, predicational and equative clauses. In contrast, identificational clauses, despite their initial resemblance to specificational clauses, are argued not to involve inversion, therefore providing empirical support for Heller and Wolter (2008). I also present novel empirical data from Czech that show that the interpretation of the pronoun in identificational clauses is restricted by the copular agreement. In order to account for the restriction, I argue that both NPs in identificational clauses Agree with the copula via a Multiple-Agree chain (see Hiraiwa (2005)).
Keywords: copular clauses; agreement; inversion; scrambling